Oral hygiene habits and its association with dental caries among children aged 8-12 year in Libyan schools, Klang Valley, Malaysia - Abuaisha, Aisha A.; Zainuddin, Huda; Ismail, Suriani (Community Health Society Malaysia, 2016)
Background: Dental caries is a serious public health problem worldwide. Prevalence of dental caries among school children has increased in both developed and developing countries since the last few decades. The objective of this study was to determine the association of dental caries with oral hygiene habits among Libyan school children aged 8-12 years in Klang Valley, Malaysia. Methodology: A cross-sectional study was conducted in three Libyan primary schools in Klang Valley, Malaysia. Five hundred and seventy children aged 8-12 years participated. They were randomly selected using proportional stratified sampling method. Dental caries was assessed using the WHO (1987) criteria. Results: Response rate was 92.5%. The prevalence of dental caries was (55.8%), females have higher dental caries than males. Dental caries was found highly prevalent among; children their aged 10 years (64.7%), children whose father and mother have a job (58.5% and 58.7%) respectively, children whose father and mother have elementary level of education (69.6% and 61.0%) respectively, children who have poor oral hygiene (99.0%). Chi square test showed significant association of dental caries with age group, father’s education level and oral hygiene habits. Logistic regression analysis identified young age (OR=0.085, 95% Cl: 0.017-0.434) and poor oral hygiene (OR=0.001, 95% Cl: 0.00-0.009) were significant predictors of dental caries among children. Conclusions: Prevalence of dental caries is associated with oral hygiene habits of children in this study. Health education on good oral hygiene habits should be emphasized among younger Libyan school children.